Structural design in architecture - Salvadori, Mario; Levy, Matthys (New Jersey : Prentice-Hall, 1981)
The favor encountered by the first edition of Structural design in architecture, including several translations, and recent new international developments in structural design convinced us of the advisability if preparing this revised edition in order to make the book more useful to practicing engineers and architects as well as to engineering and architectural students.
Loads -- Structural materials -- Straight structural elements under direct stress -- Beams -- Beam-columns and buckling -- Trusses -- Frames -- Torsion -- Cables -- Arches -- Plane grid systems -- Plates -- Stress redistribution and plastic design -- the Geometry of shell surfaces -- Membranes -- Membrane stresses in shells -- Bending and buckling of shells -- Space frames.
Includes index.
Keywords: STRUCTURAL DESIGN